Cheaper by the dozen - Gilbreth, Frank B. (Frank Bunker), 1911-; Carey, Ernestine Gilbreth; McKay, Donald, 1895-1974 (New York : Bantam, 1988)
A memoir by two children of the Gilbreth clan recounting the lives of their parents, Frank Bunker Gilbreth and Lillian Moller Gilbreth, discussing their careers as industrial engineers, work with scientific management, and the adventures they encountered raising a family with twelve children.
A Bantam starfire book"--T.p. verso.
Wilson's Junior High School.
Wilson's Senior High School.
Wilson's Junior High School, September 1995.
Wilson's Senior High School, November 1997.
6.6
Keywords: Gilbreth, Frank Bunker, -- 1868-1924.; Gilbreth, Lillian Moller, -- 1878-1972.; Gilbreth, Frank Bunker, -- 1868-1924.; Gilbreth, Lillian Moller, -- 1878-1972.; Gilbreth, Frank Bunker, -- 1868-1924.; Gilbreth, Lillian Moller, -- 1878-1972.; Galbraith family; Galbraith family; Galbraith family; Industrial engineers -- Biography; Industrial engineering; Industrial engineering -- Biography